KETERSEDIAAN GROUND SUPPORT EQUIPMENT DAN KINERJA OPERATOR RAMP SERVICES DI BANDAR UDARA SOEKARNO HATTA - Muhammad Arif Hernawan; Sinta Dwi Putri; Suprihadi Suprihadi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The aim of this study is to analyze the effect of the equipment availability towards the operator’s performance. The data collection method used in this study was questionnaire that was spread out to 30 respondents using saturated sample technique. There were 30 samples used and data processed taken from the questionnaire. The data analysis method of regression, correlation analysis, determinant coefficient and hypothesis testing were also used in this study. The result of the study shows that there is a positive effect of the equipment availability towards operator’s performance which is shown by the simple linear line of Y= 22,898 + 0.461 X. It means, there is Y value change of 0.461 times X at 22,898 constants in every one-value change of X variable. Based on the correlation analysis of r=0,421, there is a moderate effect of X variable to Y variable. Determinant coefficient testing result shows a value of 17.72% for the contribution effect of the equipment availability towards the operator’s performance. Meanwhile, there is value of 82.28% for the effect of other factors which are not analyzed in this study. Furthermore, the result of the hypothesis testing shows that t-score = 2,475 and t-table= 1,701 or t score > t table, which means H0 is rejected and Ha is accepted. It is concluded that there is a significant effect between the equipment availability and the operator’s performance.